2019
DOI: 10.1038/s41598-019-50751-7
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Variability Increases 30-Day Readmission Rates in Patients with Type 2 Diabetes Hospitalized in Department of Surgery

Abstract: Glucose variability is common among hospitalized patients with type 2 diabetes mellitus (DM). I investigated to assess the variability of glucose in patients with type 2 DM accounts for in-hospital readmission rates in department of Surgery. I retrospectively analyzed 206 patients with type 2 DM, who was admitted to our hospital for surgical interventions and re-admitted within 30 days after discharge. I also enrolled 610 age, sex and diabetic duration matched patients with type 2 DM, as control. Outcomes meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…However, it is worth mentioning that we also came across a few studies that either showed mixed results or did not find any conclusive relationship between HbA1c and SSI [11]. In a 2019 study, the probability of developing surgical complications or readmission with respect to gender, age, or presence of hypertension was found to be nonsignificant [9]. Furthermore, no association between the type of wound and HbA1c levels was found in our study.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…However, it is worth mentioning that we also came across a few studies that either showed mixed results or did not find any conclusive relationship between HbA1c and SSI [11]. In a 2019 study, the probability of developing surgical complications or readmission with respect to gender, age, or presence of hypertension was found to be nonsignificant [9]. Furthermore, no association between the type of wound and HbA1c levels was found in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…A study done by Kopp Lugli et al found an overall 4.1 times increased risk of developing SSI [4]. Raised HbA1c preoperatively is linked with an increased risk of infection, length of hospital stay and readmission in 30 days [9]. However, it is worth mentioning that we also came across a few studies that either showed mixed results or did not find any conclusive relationship between HbA1c and SSI [11].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Decreasing glucose variability during admission for surgery is essential for patients with type 2 diabetes to reducing re-admission rates and length of stay. Glycated hemoglobin (HBA1c) may also identify patients at higher risk of postoperative complications and the possibility of re-admission (8). Regular preoperative inpatient blood glucose monitoring and management can improve intraoperative and postoperative glycemic control and reduce the incidence of hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%